Retraction notice to "Fetus-in-fetu in Botswana" [J Ped Surg Case Rep 24 (2017) 46-48] - Goutam Chowdhury; Francis Msume Banda (Elsevier, 2020)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal).This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy).This article has been retracted at the request of the Editor in Chief. The authors used photographs and materials without the permission of the copyright holders. (Box 6).